PERLINDUNGAN HUKUM KONSUMEN LISTRIK PRABAYAR DI MAGELANG - Maulaya Adhiansyah, Siti Vickie Dina; Heniyatun, Heniyatun; Sulistyaningsih, Puji (Fakultas Hukum Universitas Muhammadiyah Magelang, 2017)
Along with the development of technology, PT. PLN (Persero) has developed a product called